la escultura como medio de concientización del maltrato animal - Sanchez Sanchez, Oscar Manuel (Machala: Universidad Tecnica de Machala, 2024)
This thesis, entitled "Art as a Means of Raising Awareness about Animal Abuse," underscores the significant relevance of art as a fundamental pillar through which artists can intervene in various ways, highlighting realities that are often overlooked or insufficiently addressed by society. The research emphasizes the unique capacity of art, in its diverse expressive forms, to become a powerful tool for sensitizing society to the issue of animal abuse. The análisis delves into the singular ability of art to convey complex messages in a creative and visual manner, providing a platform for the expression of emotions, ideas, and perspectives related to this critical topic. The title itself, "Art as a Means of Raising Awareness about Animal Abuse," encapsulates the essence of the study by emphasizing the crucial role of art as a catalyst for social awareness. Throughout the work, the exploration revolves around how artists use their creations to illustrate instances of animal abuse, aiming to evoke empathy and encourage reflection in the audience. Various forms of art, such as painting, sculpture, photography, and performance, are meticulously examined, showcasing how each uniquely contributes to the representation of the theme. The research reveals that these artistic expressions not only inform but also persuade the audience, creating an emotional connection that stimulates reflection and potentially leads to a change in attitude and behavior. The detailed analysis of these artistic manifestations aims not only to inform but also to persuade the audience, fostering a deep emotional connection that encourages profound reflection and, potentially, substantial changes in attitudes and behaviors towards animal protection. In conclusion, this work highlights the ability of art not only to document and represent animal abuse but also to trigger a profound impact on societal perception and collective awareness regarding the ethical and responsible addressing of this issue. The research advocates for the crucial role of art in inspiring concrete actions towards the protection and well-being of animals.
El trabajo de titulación, bajo el título "El Arte como Medio de Concientización del Maltrato Animal", subraya la significativa relevancia del arte como un pilar fundamental mediante el cual los artistas pueden intervenir de diversas maneras, destacando realidades que, con frecuencia, son pasadas por alto o no reciben la debida atención por parte de la sociedad. Esta investigación destaca la capacidad única del arte, en sus diversas formas expresivas, para convertirse en una herramienta poderosa en la sensibilización de la sociedad acerca de la problemática del maltrato animal. El análisis se adentra en la singular habilidad del arte para transmitir mensajes complejos de manera creativa y visual, proporcionando una plataforma para la expresión de emociones, ideas y perspectivas relacionadas con este tema crítico. El título mismo, "El Arte como Medio de Concientización del Maltrato Animal", encapsula la esencia del estudio al enfatizar la función crucial del arte como catalizador para la concientización social. A lo largo del trabajo, se explora la manera en que los artistas utilizan sus obras para ilustrar situaciones de maltrato animal, buscando despertar empatía y promover la reflexión en el espectador. Se examinan detalladamente las diversas formas de arte empleadas, como la pintura, la escultura, la fotografía y la performance, evidenciando cómo cada una contribuye de manera única a la representación de la temática. La investigación revela cómo estas expresiones artísticas no solo informan, sino también persuaden a la audiencia, generando una conexión emocional que impulsa a la reflexión y, potencialmente, a un cambio de actitud y comportamiento. El análisis meticuloso de estas manifestaciones artísticas no solo tiene como objetivo informar, sino también persuadir a la audiencia, generando una conexión emocional que impulsa a la reflexión profunda y, potencialmente, a un cambio sustancial de actitudes y comportamientos hacia la protección de los animales. En conclusión, este trabajo destaca la capacidad del arte no solo para documentar y representar el maltrato animal, sino también para desencadenar un impacto profundo en la percepción social y en la concientización colectiva sobre la importancia de abordar esta problemática de manera ética y responsable. La investigación aboga por el papel crucial del arte en inspirar acciones concretas hacia la protección y el bienestar de los animales.
Keywords: ARTE; CONCIENTIZACION; MALTRATO ANIMAL; SENSIBILIZACION; EMPATIA; SOCIEDAD; REFLEXION